The Presence of Pretreated Lignocellulosic Solids from Birch during Saccharomyces cerevisiae Fermentations Leads to Increased Tolerance to Inhibitors – A Proteomic Study of the Effects - Koppram, Rakesh (PLoS One, 2016)
The fermentation performance of Saccharomyces cerevisiae in the cellulose to ethanol conversion process is largely influenced by the components of pretreated biomass. The insoluble solids in pretreated biomass predominantly constitute cellulose, lignin, and -to a lesser extent- hemicellulose. It is important to understand the effects of water-insoluble solids (WIS) on yeast cell physiology and metabolism for the overall process optimization. In the presence of synthetic lignocellulosic inhibitors, we observed a reduced lag phase and enhanced volumetric ethanol productivity by S. cerevisiae CEN.PK 113-7D when the minimal medium was supplemented with WIS of pretreated birch or spruce and glucose as the carbon source. To investigate the underlying molecular reasons for the effects of WIS, we studied the response of WIS at the proteome level in yeast cells in the presence of acetic acid as an inhibitor. Comparisons were made with cells grown in the presence of acetic acid but without WIS in the medium. Altogether, 729 proteins were detected and quantified, of which 246 proteins were significantly up-regulated and 274 proteins were significantly down-regulated with a fold change≥1.2 in the presence of WIS compared to absence of WIS. The cells in the presence of WIS up-regulated several proteins related to cell wall, glycolysis, electron transport chain, oxidative stress response, oxygen and radical detoxification and unfolded protein response; and down-regulated most proteins related to biosynthetic pathways including amino acid, purine, isoprenoid biosynthesis, aminoacyl-tRNA synthetases and pentose phosphate pathway. Overall, the identified differentially regulated proteins may indicate that the likelihood of increased ATP generation in the presence of WIS was used to defend against acetic acid stress at the expense of reduced biomass formation. Although, comparative proteomics of cells with and without WIS in the acetic acid containing medium revealed numerous changes, a direct effect of WIS on cellular physiology remains to be investigated.